Sample size for half-sib family evaluation in maize - Palomino, Edwin Camacho; Ramalho, Magno Antônio Patto; Ferreira, Daniel Furtado (Pesquisa Agropecuaria Brasileira, 2000)
This work had the aim to verify the effect of the number of plants per plot in the evaluation of half-sib families. For that, 25 half-sib families of CMS-39 were evaluated with the experimental design being a simple lattice, 5 x 5, with two replications. Each plot was constituted by three lines with 10 m of length. Each plot was subdivided in sub-plots with five plants, being discarded extremities. Associating the contiguous sub-plots it was possible to simulate 270 variance analyses, with the number of plants per plot varying from 5 to 135. Genetic and phenotypic parameters were estimated with their respective errors. Expected selection response yield was also simulated for each sample size. In this simulation, it was verified that the number of plants per plot affected experimental precision. As larger was the number of plants, more accurate were the experiments; plots with the same number of plants, even so distributed in two or three lines, provide greater experimental precision. The selection expected response decreases with the increase in the number of plants per plot.